Strategic Marketing Practices and Non- Financial Performance of Selected Manufacturing Firms in Lagos State, Nigeria - Adegboyega Onikoyi, Idris; Toyin Olaniyan, Solomon; Oladimeji Adenuga, Johnson; Jumoke Zubair, Opeyemi (British Journal of Marketing Studies, 2020)
Manufacturing companies in Lagos State has been experiencing unprecedented challenges in the globalized working surroundings that result in organisation recording low business turnover which is leading to the closure of the companies or relocating to neighboring African Country. The study, therefore, seeks to examine the strategic marketing practices and non-financial performance of selected manufacturing firms in Lagos State. A descriptive research design was adopted. The population of the study was fifty – six (56) manufacturing companies in Lagos State, out of which five (5) manufacturing companies that were strictly into food and beverages, who have reputation for making products of the best quality were selected. Each of the five (5) companies selected, an average of twenty (20) that has information to provide was used except Unilever Nigeria plc that has total numbers of twenty-one (21) staff in strategic position giving the total number of one hundred and one (101), consisting strategic managers and subordinates of food and beverages companies were used as sample size. The study hence employed the purposive sampling technique to arrive at tenable sample size. Multiple Regression and Correlation Analysis were used to analyse the data obtained. Findings show that there was a positive relationship between strategic marketing practices and the performance of selected manufacturing companies in Lagos State. Furthermore, with variables statistically significant at 95% confidence limit and sig 0.000, meaning that there was a significant correlation between the environmental scanning and business expansion of manufacturing companies in Lagos State and with R2 value = (0.505), segmentation strategy has an impact on business expansion in the selected firms. Therefore, the study recommended that manufacturing companies should have a clear understanding of both the internal and external environments through constant monitoring and evaluation of the environment. Also, manufacturing companies are expected to focus on their segmentation marketing strategy activities.